Economias de aglomeração nas atividades econômicas dos municípios brasileiros nos anos de 2000 e 2009: evidências a partir de equações salariais - Amarante, Patrícia Araújo (2011)
The present study aims to obtain empirical evidence of agglomeration economies on economic activities of municipalities in the years 2000 and 2009. To do so, it is employing two complementary techniques applied to data from RAIS. At first, through the Exploratory Analysis of Spatial Data, it appears that there is some kind of spatial association in the tested variables such as spatial agglomerations or homogeneous regions (clusters) and atypical observations (outliers). Evidence obtained point to high values of autocorrelation in the municipalities of South and Southeast area and low values in the North and Northeast. In the second part, devoted to estimation of the econometric model are used to formulate wage equations based on a microeconomic model developed by Fingleton (2003), under the precepts of Urban Economics, where the main hypothesis points to a positive relationship between wage differentials and labor productivity. The results from the technique of instrumental variables via 2SLS and GMM, suggest that variations in wage rates of the Brazilian municipalities are significantly and positively related to the spatial concentration of economic activity and the spillover efficiency levels between areas that are geographically close, corroborating to Jacobs theory about the economies of urbanization.